Branch Grading as a Framework to Improve Business Growth and Bank Branch Performance - Jacoub, Yutrizal; Syabarrudin, Agus (Santoso Academy Network, 2025)
This study examines the impact of implementing a branch grading system on business performance across 46 branches of Bank